Peran Guru PAI dalam Menanamkan Karakter Religius dan Disiplin pada Peserta Didik SDN 02 Penanggungan Banjarnegara - Fatkhurrohman Fatkhurrohman; Astutining Dyah Wulandari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research is based on the fact that the cultivation of religious character and discipline is very important for guiding children's lives in the future and for preparing students to enter the next level. The two character inculcations in question at SDN 02 Penanggungan have a very close relationship and are mutually beneficial for students at SDN 02 Penanggungan who have succeeded in instilling these two characters. However, there are still obstacles in instilling this religious and disciplined character. Therefore, it is important to look for methods that can help students to implement more religious and disciplined characters in this school. Because these two characters can make students have a religious and polite nature in carrying out their lives every day. The purpose of this research is how the role of Islamic Religious Education teachers is in instilling this religious character and discipline well and being implemented by students. Because the character possessed by students at SDN 02 Penanggungan, including going to school in the middle of the village, is still very lacking. And it is hoped that with the role of the Islamic Religious Education teacher, students will have and be able to change their character for the better. This research method uses descriptive qualitative methods. A qualitative approach is research that is used to understand social phenomena or the behavior of the participants or subjects being researched. This approach focuses on collecting data to gain detailed insight into the problems that will be researched through interview, observation and document methods. The observation method is an investigation or data collection carried out deliberately by researchers by visiting the observation site directly in a systematic manner using the senses to obtain information. Interviews are a way of collecting data by holding questions and answers with people who can provide information. The documentation method is a data collection technique by collecting and analyzing documents, both written, image and electronic documents. The results of this research are focused on cultivating religious and disciplined characters in students. This research will involve Islamic Religious Education teachers, especially teachers of other subjects, parents and students. This research will include the process of cultivating good character and measuring methods for instilling this character, students can easily apply and accept several processes to achieve the goals that teachers and students will achieve in advancing the SDN 02 Penanggungan school.